Efektifitas Azotobacter sp. dan Pseudomonas sp. sebagai Plant Growth promoting Rhizobacteria (PGPR) terhadap tanaman Tomat (Lycopersicum esculentum Mill.) pada Andisol-Lembang - Pujawati Suryatmana; Nadia Nuraniya Kamaluddin; Mieke Rochimi Setiawati (Soilrens, 2022)
The concept of balanced fertilization application is appropriate for tomato plant cultivation. However, most farmers still apply inorganic fertilizers excessively, which negatively impacts the environment and plant productivity. Alternative efforts can be made to reduce the usage for inorganic fertilizers through effective plant growth-promoting rhizobacteria (PGPR) application. This research studied the characteristics of the PGPR inoculants effectiveness (Azotobacter sp. and Pseudomonassp.) combined with NPK towards tomato in Lembang Andisol. The experimental design used was randomized block design, with three replications: A (Control), B (1 PGPR + 0 NPK), C (1 PGPR + NPK), D (1 PGPR + NPK), E (1 PGPR + NPK), F (1 PGPR + 1 NPK), G (1 PGPR + 1 NPK), H (2 PGPR + 1 NPK), I (0 PGPR + 1 NPK), J (½ PGPR +1 NPK). The results showed the treatments of C, F, and J resulted in higher total soil N content than the control treatment. Meanwhile, C and D treatment increased plant N uptake compared to control. Nitrogen uptake increased with the decrease of NPK dose application. All of the PGPR inoculation treatments with NPK combination did not increase Azotobacter sp. population and tomato yield. The yield of tomatoes per hectare showed that the PGPR inoculation at a dose of 3 l/ha (1 PGPR + NPK) increased yield by 28.7% compared to 1 NPK (150 kg/ha of Urea, 100 kg SP-36 and 50 kg/ha KCl) dose. Application of 3 l/ha of PGPR inoculant can save up to 75% of NPK usage